Organization of effective use of the AutoCAD feature in teaching descriptive geometry (Journal of Pharmaceutical Negative Results, 2022)
The paper considers the development of educational programs in the field of descriptive geometry and the organization of teaching in accordance with modern requirements. When developing new curriculums, the topics of design methods in traditional curriculums (the Monge method, projections of points, lines and planes) were placed after the topics about geometric objects. The topics of the curriculum are related to geometric objects (cube, prism, pyramid, cylinder, cone). The main purpose of this is to form ideas about geometric objects among students who are very poorly versed in descriptive geometry. Students form and develop spatial imagination, creating threedimensional images of simple geometric objects (cube, prism, pyramid, cylinder, cone, inclined cylinder, inclined cone). At the same time, students develop skills of working with computer graphics programs. As a result of the development of curriculums and the introduction of three-dimensional virtual models in AutoCAD, students’ interest in graphic geometry and the quality of assimilation indicators has increased.